Natural killer cells in skin: a unique opportunity to better characterize the many facets of an overlooked secondary lymphoid organ - Johnson, Kirsten M.; Lee, Dean A. (Frontiers in Immunology, 2025)
Natural killer (NK) cells are lymphoid-derived cells that play a critical role in bridging innate and adaptive immunity. Given their ability to recognize and directly kill targets possessing missing or altered self-proteins and to induce indirect killing via recruitment of adaptive immunity, they are in a unique position to modulate host immunologic responses. These complex immune sentinels typically circulate in the peripheral blood and/or reside in lymphoid tissues. As the largest organ, human skin functions in front line immunological defense, though it has not historically been categorized as lymphoid tissue. Whether tissue-resident ILC populations originally derive from conventional circulating NK cells, or whether they interface as developmentally distinct entities with phenotypic overlap within particular inflammatory contexts remains a subject of ongoing investigation. This review seeks to consolidate the currently available literature regarding NK cell and ILC skin homing and innate immune function in healthy vs. lesional human skin (including infection, inflammatory/autoimmune conditions, and cutaneous malignancy). Importantly, we elucidate significant gaps in the understanding of the complex role for NK cells in skin homeostasis and pathology, and posit unique opportunities the accessibility of this secondary lymphoid organ provides for translational studies to improve our understanding of cutaneous immunity.